2018
DOI: 10.1007/s00253-017-8718-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and stable isotopic evidence for the occurrence of nitrite-dependent anaerobic methane-oxidizing bacteria in the mangrove sediment of Zhangjiang Estuary, China

Abstract: Nitrite-dependent anaerobic methane oxidation (n-damo), which is mediated by "Candidatus Methylomirabilis oxyfera-like" bacteria, is unique in linking the carbon and nitrogen cycles. However, the niche and activity of n-damo bacteria in the mangrove ecosystem have not been confirmed. Here, we report the occurrence of the n-damo process in the mangrove wetland of the Zhangjiang Estuary, China. The widespread occurrence of n-damo bacteria in mangrove wetland was confirmed using real-time quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…− and CH 4 concentrations, suggesting that anaerobic NH 4 + oxidation is coupled to NO 3 − reduction and denitrification (Padilla et al, 2016;Thamdrup et al, 2019). M. oxyfera-like bacteria have also been detected in estuarine and coastal sediments, where they show great diversity and a depth-specific distribution influenced by redox potential, water content and total organic C (Lidong et al, 2014;Zhang et al, 2018). Moreover, the activity of this community in coastal sediments vary seasonally and spatially and seem to be highly influenced by NO 3 − (Shen et al, 2016;Wang et al, 2017), NH 4 + , NO 2 − (Chen et al, 2014(Chen et al, , 2015b and salinity (Chen et al, 2015a;Shen et al, 2016).…”
Section: Factors Affecting N-damo and Its Distribution In Marine Systemsmentioning
confidence: 99%
“…− and CH 4 concentrations, suggesting that anaerobic NH 4 + oxidation is coupled to NO 3 − reduction and denitrification (Padilla et al, 2016;Thamdrup et al, 2019). M. oxyfera-like bacteria have also been detected in estuarine and coastal sediments, where they show great diversity and a depth-specific distribution influenced by redox potential, water content and total organic C (Lidong et al, 2014;Zhang et al, 2018). Moreover, the activity of this community in coastal sediments vary seasonally and spatially and seem to be highly influenced by NO 3 − (Shen et al, 2016;Wang et al, 2017), NH 4 + , NO 2 − (Chen et al, 2014(Chen et al, , 2015b and salinity (Chen et al, 2015a;Shen et al, 2016).…”
Section: Factors Affecting N-damo and Its Distribution In Marine Systemsmentioning
confidence: 99%
“…Several microbial groups and transformation processes have only recently been discovered (DNRA, anammox, methane denitrification), but are often quantitatively important in N cycling. For example, a nitrite-dependent anaerobic methane-oxidizing bacterium was recently discovered in mangrove soils of the Zhangjiang estuary in China [128]. This "Candidatus Methylomirabilis oxyfera-like" bacterium is unique in linking the carbon and nitrogen cycles.…”
Section: The Nitrogen Cycle In Soilsmentioning
confidence: 99%
“…However, the uptake of ammonium and nitrate by plants was down regulated under carbon limiting conditions [77]. Therefore, in deep mangrove sediments with low organic carbon content [78], the main form of nitrogen uptaken by mangrove species was assumed to be amino acids. In support of this assumption, our metagenomic sequencing analysis showed that with the increasing depth of mangrove sediments, both biological nitrogen xation and ammonia assimilation pathways were enhanced, whereas ammonia and organic nitrogen loss by denitri cation and organic nitrogen decomposition pathways was weakened.…”
Section: Discussionmentioning
confidence: 99%